(3GdeHgL aj Yde GdWHs - (3GdTQja efUhQ GdMSjfjs; (3GdTQja efUhQ GdMSjfjs
(3ChdgG (B:s
(3HYO GdMeO ddg hUMHg GdefJNHjf GLeYjf GeG HYO ajbhd GdVYja GdeMJGL Edi QMeI QHg s
(3BNQgG (B:s
(3hjfJaY ai TQGH LjO GdLhgQ SHY CjGe hjWHN HQab hjUai hjbhe bdjdG hGddg GYde HGdUhGH Je gPG GdcJGH s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3JQLeI(B/(3fbds
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs